The nearly ghost baby - Huddy, Delia (London : A & C Black, 1996)
A beach house in Cornwall seems like an ideal holiday spot for Lisa and her family. But then they learn about an old tragedy which still haunts the house ; Lisa isn't the only one who has difficulty sleeping peacefully.
Primary
Keywords: Fiction; Ghosts -- Fiction